INVISIBLE VINNIE - NIMMO, JENNY (THE RANDOM HOUSE GROUP CHINA, 2012)
Rose wishes Zack wasn't such a big bully. He's always teasing her at school. With the help from her Uncle Vinnie and the classroom pet rat, Rose is ready to teach Zack a lesson he'll never forget. Suggested level: primary
shelving location "K"
for class 1/2/3